1986
DOI: 10.3109/00365528609034637
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease: Scintigraphic, Endoscopic, and Histologic Considerations

Abstract: Radionucleotide scintigraphy and esophagoscopy with biopsy were carried out in 101 patients with symptoms strongly suggestive of gastroesophageal reflux (GER) disease. GER was visualized by scintigraphy in 86.1% of the patients. Endoscopic and histologic esophagitis were found in 68.1% and 58.4% patients, respectively, whereas both examinations taken together showed evidence of esophagitis in 82%. Histologic evidence of esophagitis was found in nearly all patients with severe endoscopic changes and in 43.7% pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“… 10 Combining tests can improve sensitivity. 11 For this reason, we chose to define the presence of GERD with positive results in any one of these four tests.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Combining tests can improve sensitivity. 11 For this reason, we chose to define the presence of GERD with positive results in any one of these four tests.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies demonstrated that the use of acidified food increased the correlation between food and acid reflux, leading to the conclusion that gamma scintigraphy was detecting the reflux of neutral materials which could not be detected by pH monitoring 12 , . 13 By 1986, largely due to the work of Kaul and co‐workers, scintigraphic reflux could be detected in 92% and 79% of the patients with and without histologic evidence of oesophagitis 14 . By 1990, the lack of correlation between pH monitoring and reflux of radiolabelled gastric contents as measured by scintigraphy became accepted as accurate findings and the conclusion was drawn that extended pH monitoring and scintigraphy measured different pathophysiologic phenomena and they detected reflux under different conditions 3 , .…”
Section: Discussionmentioning
confidence: 99%
“…Each modality has advantages and limitations and there is no absolute gold standard for the diagnosis of GERD. Endoscopy has a sensitivity of only 30–50% in patients who present with typical heartburn 2–5 . This is because the majority of patients who present with classical symptoms of GERD may not have visible changes of esophagitis.…”
Section: Introductionmentioning
confidence: 99%